FAR INFRARED-LASER LINES AND ASSIGNMENTS OF CH3OH - A REVIEW - Moruzzi, G.; Moraes, João Carlos Silos [UNESP]; Strumia, F. (Plenum Publ Corp, 1992)
Methyl alcohol is the most important lasing molecule in the Far-Infrared (FIR) spectral region, and the most widely used for investigation and for applications. Since the last critical review of 1984, over seventy papers have been published dealing with the FIR laser lines and the infrared spectroscopy of CH3OH. In 1984 we could list about 330 FIR laser lines, 98 of which were measured in frequency and 105 assigned. Since then more than 70 papers were published increasing the number of the known laser lines to 575 (103 measured in frequency). Also the FIR and IR spectroscopy was largely improved thanks to the analysis of high resolution FT spectra, and the number of the correctly assigned laser lines has been increased to 224. The wavenumbers of the assigned lines can now be predicted with an accuracy of about 0.001 cm-1 or better, thus approaching the accuracy of the experimental frequency measurements.
Keywords: FIR LASER LINES; CH3OH,SPECTROSCOPY; LASER FREQUENCY MEASUREMENTS